Measuring social competencies - Ingrid Schoon (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
What are social competencies, how can they be measured, and do they remain stable over time. This contribution examines the difficulties in conceptualising and measuring social competencies at different developmental stages and in a changing social context. Existing measures and available data sources are reviewed and recommendations for future developments in data provision, data usage and access are made.
Keywords: 330; Social competence; social skills; social relationships and interaction